2017
DOI: 10.20944/preprints201707.0042.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health Risk Assessment of VOCs from Surgical Smoke

Abstract: Surgical smoke is produced by energy-based surgical instruments. The airborne volatile organic compounds (VOCs) from surgical smoke may have potential health risk. This study aimed to evaluate the evidence for the harmful effects on the operating theater staff. An internationally recognized evaluation model of health risk assessment (HRA) was adapted to preliminarily assess the health risks caused by VOCs in surgical smoke. Results of HRA indicated that non-carcinogenic risk indexes of VOCs did not exceed one,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…In the study of Choi et al (2014), cancer risk assessment of chemicals in surgical smoke revealed that toluene and xylenes are to be included in the group of non-carcinogenic chemicals which are still hazardous to health. She et al (2017) report that surgical smoke generated in the laboratory using pork and pig liver does not exceed the threshold values of toluene, ethylbenzene, xylene, and naphthalene in terms of non-carcinogenic health risks associated with indoor air quality. In the same way, although toluene, ethylbenzene, xylene, and naphthalene were measured at higher values at the time of surgery than before and after surgery, their average values remained below the set limit value in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Choi et al (2014), cancer risk assessment of chemicals in surgical smoke revealed that toluene and xylenes are to be included in the group of non-carcinogenic chemicals which are still hazardous to health. She et al (2017) report that surgical smoke generated in the laboratory using pork and pig liver does not exceed the threshold values of toluene, ethylbenzene, xylene, and naphthalene in terms of non-carcinogenic health risks associated with indoor air quality. In the same way, although toluene, ethylbenzene, xylene, and naphthalene were measured at higher values at the time of surgery than before and after surgery, their average values remained below the set limit value in this study.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of cancer risk assessment studies conducted with benzene, it is reported to increase the risk of cancer (Moslem et al, 2020). She et al (2017) stated that benzene also has a detrimental effect on human health, and that prolonged exposure to surgical smoke poses a great cancer risk. In et al (2015) examined living cells in surgical smoke by cauterizing cancer tissue and reported that the cancer cells found in surgical smoke were the same as the cancer cells cauterized, and when they applied these cancer cells in the surgical smoke to the back of rats, they observed them to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Cerrahi dumanın içerisinde ayrıca fenol, etanol, klorofom, benzen, toluen, etilbenzen, ksilenler venaftalin gibi 150 toksik kimyasal maddenin bulunduğu belirtilmektedir 11,12 . Cerrahi dumanın içinde bulunan bu kimyasallar genetik mutasyonların ve kanserin tetikleyicisi olabilmektedir.…”
Section: Cerrahi Dumanın Kimyasal Ve Toksik Etkileriunclassified
“…Filtre içindeki hava akımı saniyede 1-2 cm'dir. ULPA filtre ya da ultra düşük penetrasyonlu hava filtresi 0,12 mikron ve daha büyük partikülleri uzaklaştırmada %99,9 verimlilik oranına sahiptir 12 . Günümüzde ameliyathanelerde yeni yeni kullanılmaya başlayan duman tahliye sistemleri taşınabilir cihazlara göre daha sessiz ve çekiş gücü kuvvetlidir 21 .…”
Section: Cerrahi Dumandan Korunmaya Yönelik Alınması Gereken öNlemlerunclassified
See 1 more Smart Citation